INCORPORATING HIGHER-ORDER THINKING SKILLS IN ENGLISH LESSON PLANS FOR SENIOR HIGH SCHOOL - Rosevinda Nabila Putri; Siti Drivoka Sulistyaningrum (University of Muhammadiyah Malang, 2021)
Since high order thinking skill is the most significant skills in the twenty-first century, there has been a lot of interest in it nowadays. Incorporating HOTS in the educational field, particularly in assessment, has been broadly employed. However, there is a lack of lesson plans that incorporates high-order thinking skills. This current study aims to explore the higher order thinking skills in lesson plans, particularly English, at Senior High School in Indonesia. This research employs a content analysis approach. A systematic content descriptive text methodology was used to analyse the data, which was based on Anderson and Krathwohl’s Taxonomy's cognitive levels. The data source of this study are 5 English lesson plans at two Senior High Schools in Jakarta. The result of the study indicates that HOTS levels C4, C5, and C6 are found in lesson plans, learning objectives, and learning activities. The result also reveals that the lesson plan needs further revisions to meet the HOTS standards that have been incorporated into the curriculum and national education strategy.